Selective recruitment of NAT10-catalyzed ac4C-modified mRNAs into stress granules by poly(A)-binding protein promotes mRNA stability and plant heat stress tolerance - Wanhong Zhang; Yanxiao Bu; Yubing Jiao; Yingwen Wang; Lili Shen; Ying Li; Binna Lv; Tzu-Chieh Ho; Yih-Cherng Liou; Chin-Kuo Chen; Fei Han; Robert Y.L. Wang; et al. (Molecular Plant, 2026)

Nitric oxide indicates the response of Chlorella sp. to ocean warming and its potential mechanisms - Kuo Li; Zheng-Xin Hu; Ying-Shun Wang; Hui-Min Jian; Pei-Feng Li; Chun-Ying Liu; Jing-Wen Hu; Gui-Peng Yang (Marine Biology, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Heme Iron Polypeptide Resolves Iron-deficiency Anemia in Rats and Mice - Yue He; Jacob S. Shine; Sitara Sriram; Melissa Fraga; Li-Ying Kuo; Jennifer K. Lee; Xiaojing Yuan; Iqbal Hamza; James F. Collins (Biological Trace Element Research, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Microbial dynamics of wild and cultured Sinularia flexibilis: Implications for coral aquaculture - Li-Guo Zheng; Kuei-Hung Lai; Ping-Jyun Sung; You-Ying Chen; Jimmy Kuo; Jui-Hsin Su; Mohamed El-Shazly (Aquaculture, 2026)

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

Tyramine injection enhances immune function and disease resistance in Penaeus monodon - Wan-Lin Tsai; Li-Yang Hsu; Cheng-Ying Li; Hsin-Wei Kuo; Winton Cheng (Fish & Shellfish Immunology, 2025)

“d-f electron ladder” accelerates dynamic reconstruction of bimetallic sulfides for efficient oxygen evolution in seawater electrolysis - Kuo Wei; Ruijia Xie; Mengdi Li; Feng Chen; Lu Zhou; Yaxu Zhao; Guiqing Xu; Yuanzhe Wang; Ying Meng; Faming Gao (Chemical Engineering Journal, 2025)

Waste cotton thread-derived SnO2 microfibres for enhanced sensing to trace triethylamine and application in meat freshness detection - Jing-Han Wang; Xiao-Na Zhang; Kuo Lin; Wen-Xiao Li; Bao-Yu Song; Fei Ye; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2025)

Answer to comments on “Bamboo ecosystem services in 25 years: a systematic literature review of trends, insights, and knowledge gaps” - Chong-En Li; Shih-Yu Lee; Yi-Ying Chen; Shih-Yun Kuo; Mei-Hua Yuan (Environmental Science and Pollution Research, 2025)

Bamboo ecosystem services in 25 years: a systematic literature review of trends, insights, and knowledge gaps - Chong-En Li; Shih-Yu Lee; Yi-Ying Chen; Shih-Yun Kuo; Mei-Hua Yuan (Environmental Science and Pollution Research, 2025)
While bamboo offers various benefits to people, existing reviews on the current state of knowledge and research trends regarding its ecosystem services remain limited. This study aims to systematically review the literature on bamboo ecosystem services, focusing on temporal and geographic patterns, thematic trends, and methodological approaches, as well as the exploration of synergies and trade-offs. It adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines and includes an analysis of 56 relevant studies indexed in Scopus. This review shows a recent growing academic interest in bamboo ecosystem services. Research is primarily concentrated in regions where bamboo is commonly found, shaped by regional research capacity, and characterized by both locally led efforts and externally conducted studies. Keyword and co-occurrence analyses identify three main research clusters focused on the quantitative assessment, qualitative investigation and economic valuation of ecosystem services. Methodologically, studies tend to rely on plot sampling for data collection, apply indices for analysis, and present findings through mapping and statistical techniques. Among ecosystem service categories, regulation and maintenance services receive the most attention. However, interactions among services remain underexplored, with research on synergies and trade-offs still limited. These findings provide valuable insights for bamboo forest management and indicate future research directions that merit deeper exploration.

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Elevated atmospheric CO2 promotes the contribution of autotrophic nitrification to N2O emissions in a typical summer maize field - Fen Ma; Yingchun Li; Ying Liu; Libing Dong; Xue Han; Xinyue Zhang; Kuo Li; Liping Guo (European Journal of Agronomy, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Injection administration of mangosteen, Garcinia mangostana, husk extract enhances physiological and immune-neuroendocrinological regulation of Macrobrachium rosenbergii - Suwaree Kitikiew; Zheng-Xiang Chieng; Cheng-Ying Li; Hsin-Wei Kuo; Winton Cheng (Fish & Shellfish Immunology, 2023)

Dietary administration of mangosteen, Garcinia mangostana, peel extract enhances the growth, and physiological and immunoendocrinological regulation of prawn, Macrobrachium rosenbergii - Hsin-Wei Kuo; Cheng-Ying Li; Zheng-Xiang Chieng; Winton Cheng (Fish & Shellfish Immunology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

The evolution of coal, examining the transitions from anthracite to natural graphite: a spectroscopy and optical microscopy evaluation - Liang Yuan; Qinfu Liu; Kuo Li; Ying Quan; Xiaoguang Li; Jonathan P. Mathews (Frontiers of Earth Science, 2023)

Ultrasonic-assisted stewing enhances the aroma intensity of chicken broth: A perspective of the aroma-binding behavior of fat - Jun Qi; Chuan-kang Jia; Wen-wen Zhang; Hui-min Yan; Qing-yuan Cai; Xiu-ning Yao; Kuo Xu; Ying Xu; Wen-ping Xu; Guo-yuan Xiong; Mei-qi Li (Food Chemistry, 2023)

The immunostimulatory effects of Theobroma cacao L. pod husk extract via injection and dietary administrations on Macrobrachium rosenbergii and its resistance against Lactococcus garvieae - Hsin-Wei Kuo; Cheng-Ying Li; Yun-Ru Chen; Winton Cheng (Fish & Shellfish Immunology, 2023)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Design and synthesis of novel 7-[( N -substituted-thioureidopiperazinyl)-methyl]-camptothecin derivatives as potential cytotoxic agents - Zi-Long Song; Guan-Zhou Yang; Jun-Cai Li; Ying-Qian Liu; Chen-Jie Yang; Masuo Goto; Zhi-Jun Zhang; Susan L. Morris-Natschke; Hua Liu; Kuo-Hsiung Lee (Natural Product Research, 2020)

The Taiwan WRF Ensemble Prediction System: Scientific Description, Model-Error Representation and Performance Results - Chih-Hsin Li; Judith Berner; Jing-Shan Hong; Chin-Tzu Fong; Ying-Hwa Kuo (Asia-Pacific Journal of Atmospheric Sciences, 2020)

ZAK induces cardiomyocyte hypertrophy and brain natriuretic peptide expression via p38/JNK signaling and GATA4/c-Jun transcriptional factor activation - You-Liang Hsieh; Ying-Lan Tsai; Marthandam Asokan Shibu; Chia-chi Su; Li-Chin Chung; Peiying Pai; Chia-Hua Kuo; Yu-Lan Yeh; Vijaya Padma Viswanadha; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2015)

Design, synthesis, crystal structure, bioactivity, and molecular docking studies of novel sulfonylamidine-derived neonicotinoid analogs - Liu Yang; Yong-Long Zhao; Chun-Yan Zhao; Huan-Huan Li; Mei-Juan Wang; Susan L. Morris-Natschke; Keduo Qian; Kuo-Hsiung Lee; Ying-Qian Liu (Medicinal Chemistry Research, 2014)

Synthesis of novel spin-labeled podophyllotoxin derivatives as potential antineoplastic agents: Part XXV - Liu Yang; Xiang Nan; Wen-Qun Li; Mei-Juan Wang; Xiao-Bo Zhao; Ying-Qian Liu; Zhi-Jun Zhang; Kuo-Hsiung Lee (Medicinal Chemistry Research, 2014)

Gelsolin (GSN) induces cardiomyocyte hypertrophy and BNP expression via p38 signaling and GATA-4 transcriptional factor activation - Wei-Syun Hu; Tsung-Jung Ho; Peiying Pai; Li-Chin Chung; Chia-Hua Kuo; Sheng-Huang Chang; Fuu-Jen Tsai; Chang-Hai Tsai; Yu-Chi Jie; Ying-Ming Liou; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2014)

MicroRNA-29a protects against acute liver injury in a mouse model of obstructive jaundice via inhibition of the extrinsic apoptosis pathway - Mao-Meng Tiao; Feng-Sheng Wang; Li-Tung Huang; Jiin-Haur Chuang; Ho-Chang Kuo; Ya-Ling Yang; Ying-Hsien Huang (Apoptosis, 2014)

The effect of the red wine polyphenol resveratrol on a rat model of biliary obstructed cholestasis: involvement of anti-apoptotic signalling, mitochondrial biogenesis and the induction of autophagy - Tsu-Kung Lin; Li-Tung Huang; Ying-Hsien Huang; Mao-Meng Tiao; Kuo-Shu Tang; Chia-Wei Liou (Apoptosis, 2012)

Effects of PGI2 analogues on Th1- and Th2-related chemokines in monocytes via epigenetic regulation - Chang-Hung Kuo; Ying-Chin Ko; San-Nan Yang; Yu-Te Chu; Wei-Li Wang; Shau-Ku Huang; Huan-Nan Chen; Wan-Ju Wei; Yuh-Jyh Jong; Chih-Hsing Hung (Journal of Molecular Medicine, 2011)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)